Effects of Javanese Ginseng Root Extracts (Talinum triangulare W.) on Thickness of Seminiferous Tubules of Male Rats (Rattus norvegicus) Exposed by Cigarette Smoke - Rifqi Misbahuddin Nur; Anung Putri Ilahika; Desy Andari (JUXTA: Jurnal Ilmiah Mahasiswa Kedokteran Universitas Airlangga, 2023)
Highlights:1. Infertility in men can be caused by smoking, the content of free radicals in cigarettes can affect male reproductive organs.2. Javanese ginseng root (Talinum triangulare w.) extract contains ginsenoside which is a natural antioxidant to reduce free radical levels inside the body.3. Javanese ginseng root (Talinum triangulare w.) extract was able to reduce free radical levels as seen from the appearance of the seminiferous tubules of male white rats exposed to cigarette smoke. AbstractIntroduction: Cigarette smoke contains various radical chemical compounds that can increase oxidative stress, which may cause lipid peroxidation in the body and affect various different organs. This study aimed to examine the effects of Javanese ginseng root extracts (Talinum triangulare W.) on the thickness of seminiferous tubules of white male rats (Rattus norvegicus) exposed to cigarette smoke.Methods: This was an experimental study with a randomized controlled method and a post-test control group design. Post-test control group design with 15 white male rats was divided into five groups: a normal group, a control group (exposed to cigarette smoke), and three treatment groups (exposed to cigarette smoke and Javanese ginseng root extract with doses of 12.5mg, 25mg, and 50mg/200grBW, respectively) for 30 days. The seminiferous tubule thickness was observed using H&E staining under a light microscope with 200x magnification in five fields view.Results: One-way ANOVA showed that Javanese ginseng root extracts significantly affected seminiferous tubule thickness (p = 0.000). With a dose of 12.5mg/200mgBW, Javanese ginseng root extract started to show a significant effect (p = 0.000) on the thickness of the epithelium of the seminiferous tubules. The group exposed to cigarette smoke had an average thickness of seminiferous tubules of 7.92 mm, the normal group had an average thickness of 9.13 mm, and treatment groups with doses 12.5mg, 25mg, and 50mg/200gBW had an average thickness of 11.85 mm, 12.7mm, and 14.69 mm, respectively.Conclusion: Javanese ginseng root extract increased seminiferous tubule thickness in white male rats exposed to cigarette smoke.